Choice of organizational structure in foreign markets : the impact of ownership and location specific determinants on the foreign direct investment behavior of Nordic firms - Larimo, Jorma (Proceedings of the University of Vaasa, 1999)
Abstract.
Keywords: investoinnit; organisaatiot; yritysmuodot; suorat investoinnit; yritykset; kansainvälistyminen; kansainväliset yritykset; ulkomaiset investoinnit; yhteisyritykset; tytäryhtiöt; företagsformer; samföretag; Ulkomaiset investoinnit; Suorat investoinnit; Yhteisyritykset; Tytäryhtiöt; Foreign investments; Direct investments; Subsidiaries; Joint ventures; Pohjoismaat; utlandsinvesteringar; direkta; organisationsstruktur